2005
DOI: 10.1212/01.wnl.0000151857.43225.49
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors and migraine

Abstract: Migraineurs, particularly with aura, have a higher cardiovascular risk profile than individuals without migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
402
17
14

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 427 publications
(453 citation statements)
references
References 38 publications
20
402
17
14
Order By: Relevance
“…The association between LRP1 and intracranial aneurysms has to our knowledge not been studied yet. Apart from the hypothesized direct causal associations, it is likely that there are common cardiovascular risk factors associated with both migraine and UIA, such as hypertension and smoking although we adjusted for these factors in our analyses (Scher et al., 2005; Vlak et al., 2013). More studies are needed to confirm our findings and to further investigate the underlying pathophysiology between the possible association between migraine and intracranial aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…The association between LRP1 and intracranial aneurysms has to our knowledge not been studied yet. Apart from the hypothesized direct causal associations, it is likely that there are common cardiovascular risk factors associated with both migraine and UIA, such as hypertension and smoking although we adjusted for these factors in our analyses (Scher et al., 2005; Vlak et al., 2013). More studies are needed to confirm our findings and to further investigate the underlying pathophysiology between the possible association between migraine and intracranial aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…The GEM population-based study reported that, compared to controls, migraineurs were more likely to smoke, less likely to drink alcohol and more likely to report a parental history of early myocardial infarction. Migraineurs with aura were more likely to have an unfavourable cholesterol profile, to have elevated blood pressure and to report a history of early onset coronary heart disease or stroke; female migraineurs with aura were more likely to be using oral contraceptives [22].…”
Section: Migraine and Strokementioning
confidence: 99%
“…Data from several studies suggest that migraine may be a risk factor for the development of stroke [3,4,[9][10][11][12] and MA may be an important risk factor for stroke in women [12,13]. The mechanisms that underlie these observations are unclear but a reasonable hypothesis could include the presence of shared risk factors as a possible cause.…”
Section: Discussionmentioning
confidence: 99%
“…There appears to be a clear correlation between migraine and stroke or other cardiovascular events in rare genetic conditions such as cerebral autosomal dominant arteriopathy with subcortical infarctions and leukoencephalopathy (CADASIL), mitochondrial encephalopathy with lactic acidosis and stroke-like episodes (MELAS) and the familial dyslipoproteinaemias [2]. Association between the common forms of migraine, stroke and other vascular risk factors has been shown in several large population-based studies [3,4]. An increase in vascular events in parents and grandparents of children with migraine compared to control subjects has been documented previously [5].…”
Section: Introductionmentioning
confidence: 99%